Means, ends and conditions of possibility. The critic reasons of abolitionism - Soto Moreno, Erika (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
This essay stands up for the need of overcoming the feminist debate concerning prostitution, by accepting that feminism can only walk towards a society where prostitution does not exist, although under no circumstances should this utopia become an excuse to trample on women who live on this practice. In this sense, the paper states as the condition of possibility of feminism the distinction between emancipating goals and alienating ones, and presents a critic analysis of arguments with which antiabolitionist positions (both liberal and pro-rights) defend the legitimacy of prostitution or even its liberating nature. Such an analysis, in addition to clearing up some confusions, carries to the conclusion that these arguments only make sense in the dominant neoliberal context, where ethical perspectives are believed obsolete, since the subject’s will is thought as sufficient condition to validate any purpose. Finally, the text sets that defending abolitionism in a theoretical ground does not exclude, in practice, a negotiation with women that prostitute themselves about the measures that may be taken in order to attend their needs and claims. This way, the proposal could be akin to an emerging “third-way” position.
Keywords: Prostitution; Sex work; Sex workers’ rights; Prostitution abolitionism; Feminist emancipation